Adenosine signaling pathways as potential therapeutic targets in respiratory disease. (October 2013) - Caruso, Massimo; Alamo, Angela; Crisafulli, Emanuele; Raciti, Cirino; Fisichella, Alfredo; Polosa, Riccardo
<x xml:space="preserve">Abstract</x> Introduction: Adenosine receptors (ARs) and their differential pattern of expression modulate a series of pleiotropic activities that are known to contribute to the control of inflammation, remodeling, and tissue repair. Consequently, pharmacological manipulation of adenosine signaling pathway is of great interest and is currently exploited as a therapeutic target for a number of respiratory diseases with several molecules with agonist and antagonist activities against known ARs being developed for the treatment of different conditions of the respiratory system. Areas covered: Herein, we will review the rational basis leading to the development of novel therapies for asthma, chronic obstructive pulmonary disease (COPD), interstitial lung disease (ILD), pulmonary arterial hypertension (PAH), and cystic fibrosis. Their most recent clinical development will be also discussed. Expert opinion: Advances in our understanding of the pathogenetic role of adenosine in respiratory diseases may be soon translated into effective treatment options. In consideration of the complex interplay driven by the different pattern of receptor distribution and/or affinity of the four known AR subtypes in specific cell types at different stages of the disease, it is likely that combination of selective antagonist/agonists for different AR subtypes will be required to obtain reasonable clinical efficacy. Alternatively, controlling the factors involved in driving adenosine concentrations in the tissue may be also of great significance.